2018
DOI: 10.18632/aging.101714
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training augments Sirt1-signaling and attenuates cardiac inflammation in D-galactose induced-aging rats

Abstract: Exercise is known to be beneficial in controlling aging associated disorders however, the consequence of long-term exercise on cardiac health among aging population is not much clear. In this study the protective effect of exercise on aging associated cardiac disorders was determined using a D-galactose-induced aging model. Eight weeks old Sprague Dawley rats were given intraperitoneal injection of 150 mL/kg D-galactose. Swimming exercise was provided in warm water for 60 min/day for five days per week. Hemato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 48 publications
(36 reference statements)
1
38
0
3
Order By: Relevance
“…Swimming exercise relieves the peripheral and central inflammation, but the mechanism has not been investigated extensively to date. It is reported that SIRT1 can inhibit nuclear factor kappa B (NF-κB) signaling pathway and suppress the systemic inflammation [11,12,31]. The NF-κB is composed of two subunits, P50 and P65, and is activated by various inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Swimming exercise relieves the peripheral and central inflammation, but the mechanism has not been investigated extensively to date. It is reported that SIRT1 can inhibit nuclear factor kappa B (NF-κB) signaling pathway and suppress the systemic inflammation [11,12,31]. The NF-κB is composed of two subunits, P50 and P65, and is activated by various inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 has various physiological functions by regulating some key targets via deacetylation, such as NF-κB and peroxisome proliferator-activated receptor γ (PPARγ) [11]. Chen WK et al [12] demonstrated that long-term aerobic exercise facilitated SIRT1 protein expression and enhanced SIRT1-related anti-aging signals. Aerobic exercise induced the expression of SIRT1 which inhibited the NF-κB pathway.…”
Section: Agingmentioning
confidence: 99%
“…Under oxidative stress conditions, the Foxo3a existing in the nucleus induces the expression of inflammatory proteins. SIRT1 protects the cell and stabilizes nDNA by deacetylating Foxo3a and attenuating its function [104] (Figure 4). SRT1720, an activator of SIRT1, ameliorates contractile dysfunction and impaired mitophagy in cardiac aging [105].…”
Section: Regulation Of Mitochondrial Biogenesismentioning
confidence: 99%
“…Long-term exercise-derived circulating EVs protect the heart from myocardial ischaemia/reperfusion injury via exosomal miR-342-5p 44 . Long-term exercise training potentially enhances silent information regulator 1 (SIRT1) signalling, attenuates cardiac inflammation, and provides cardioprotection in d -galactose-induced ageing rats 45 . Cigarette smoke-induced EVs promote thrombin generation in normal human plasma and contribute to increased cardiovascular risk in smokers 46 .…”
Section: Introductionmentioning
confidence: 99%